PENGARUH KEPERCAYAAN DAN KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN PADA E-COMMERCE LAZADA - Anjarwati, Nenih Lulu; Khatimah, Husnul (Media Riset Bisnis Ekonomi Sains dan Terapan, 2025)
This study aims to determine the influence of perception of trust and service quality on customer loyalty in e-commerce Lazada. The method used is a quantitative descriptive method. The population in this study is Lazada e-commerce consumers who live in Bekasi City and have made purchases at least 2 times or more. The data used were obtained from a questionnaire given to Lazada e- commerce consumers totaling 100 respondents via a google form (googleform). In sampling using nonprobability sampling.The results of the analysis prove that the F count value is 92.582 with a significant value of 0.000, then Ho is rejected and Ha is accepted. These results prove that trust and service quality simultaneously have a significant influence on customer loyalty e- commerce lazada. The results of the t-test obtained that X1 = 1.726 is greater than the t table (1.660) and a significant value of 0.05 means that the alternative hypothesis 1 is rejected, the conclusion is that trust partially has an effect but is not significant on customer loyalty. Then the service quality variable partially has a significant effect on customer loyalty, with the results of the t-test that X2 = 4.487 is greater than the t table (1.660) and the value does not exceed 0.05 meaning Ha2 or alternative hypothesis 2 is accepted.Keywords: Trust, Service Quality, and Purchase Loyalty